China’s Cooperation with Neighboring Developing Countries: Achievements and Challenges Ahead - Chenyang Li; Xiangzhang Yang (China Quarterly of International Strategic Studies, 2019)
Developing countries in China’s neighborhood have occupied a unique position in China’s foreign policy since the beginning of the 21st century. China’s cooperation with neighboring developing countries has been intensified due to a number of factors including, among other things, growing overall national strength, increasingly urgent development needs of neighboring countries, and extraterritorial powers’ shifting strategic focus. Over the past decades, closer economic cooperation between China and neighboring developing countries has facilitated the formation of a network of partnerships and sharpened China’s sense of global responsibility. However, multiple challenges have to be tackled before China can elevate its relations with its neighboring countries to a new level, such as inadequate protection of China’s expanding overseas interests, lingering misunderstanding and disputes between China and its neighbors, as well as interference from extraterritorial powers.